An Aspirational Move or Mistake? A Case of Emerging Market Cross-Border M&A - Sakshi Kukreja, G. C. Maheshwari, Archana Singh, (European Economic Letters (EEL), 2023)
In the wake of liberalization and globalization, several Indian firms started outbound foreign direct investments, a bulk of which was accounted for cross-border M&As. A trailblazer case has been the acquisition of Corus Group Plc., an Anglo-Dutch steel company by Tata Steel Ltd, headquartered in India. Requiring a net financing worth USD 12.9 million, the deal marked the largest emerging market cross-border acquisition. Plagued with hubris, the deal’s fortunes changed with recession setting in the steel industry. Success has been elusive. The study examines the deal performance and helps to demystify the various internal and exogenous causes of failure.